2022
DOI: 10.1039/d2dt00200k
|View full text |Cite
|
Sign up to set email alerts
|

Use of vibrational spectroscopy to identify the formation of neptunyl–neptunyl interactions: a paired density functional theory and Raman spectroscopy study

Abstract: Actinyl-Actinyl interactions (AAIs) occur in pentavalent actinide systems, particularly for Np(V), and lead to complex vibrational signals that are challenging to analyze and interpret. Previous studies have focused on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…Additionally, efforts will further be needed to understand related Np and Pu systems to provide added insights into the electronic structure of f -block elements. Only a handful of related Np compounds have been reported in the literature, but these systems display enhanced NCIs compared to their uranyl counterparts. ,,, However, the experimental determination of Δ H f of neptunyl can be far more challenging than that of uranyl systems due to limited availability, high cost, and the increased radioactivity of neptunium-237.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, efforts will further be needed to understand related Np and Pu systems to provide added insights into the electronic structure of f -block elements. Only a handful of related Np compounds have been reported in the literature, but these systems display enhanced NCIs compared to their uranyl counterparts. ,,, However, the experimental determination of Δ H f of neptunyl can be far more challenging than that of uranyl systems due to limited availability, high cost, and the increased radioactivity of neptunium-237.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of these equatorial ligands leads to additional electron donation to the An­(VI) metal center and weakening of the UO yl bond, an effect often observed through red-shifting of the ν 1 and ν 3 modes in Raman and IR spectroscopy. UO yl bond weakening is known to increase the Lewis basicity of the axial oxo groups, enhancing their ability to interact with Lewis acids through different non-covalent interactions (NCIs) . These second-sphere NCIs, including Coulombic, hydrogen bonding, and halogen bonding, can influence the overall chemical and physical properties of the material, including structural topologies, redox potentials, , and activation of vibrational modes. …”
Section: Introductionmentioning
confidence: 99%
“…The actinyl bond is both Raman-active, ν 1 , the symmetric stretching of the dioxo cation, and infrared (IR)-active, ν 2 , the bending mode, and ν 3 , the asymmetric stretching mode. Early studies of uranyl complexes developed empirical relationships between the observed vibrational frequencies, the −yl bond length, and the nature of the equatorial ligand interactions highlighting the correlation between a lengthening uranyl bond and a lower vibrational frequency consistent with Badger’s rules. Subsequent studies, including our own, have extended these studies to the transuranium molecules with the goal of understanding the periodic properties of the actinyl ions beyond uranium. …”
Section: Introductionmentioning
confidence: 99%
“…Effective charges in uranyl(VI), for example, are +3.2e on U and −0.6e on O yl , i.e., [ 0.6− O�U 3.2+ �O 0.6− ] 2+ . 3,4 Condensed phase AAIs are prevalent for pentavalent actinyls like neptunyl(V), 5,6 whereas less common for dipositive hexavalent actinyls due to greater Coulombic repulsion. 2,7−9 Small gas-phase complexes are well suited for high-level ab initio electronic structure computations to provide elucidation that may be relevant to understanding more complicated condensed-phase systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The AAI is between polar actinyl cations, [ δ− OAn (2δ+ n )+ O δ− ] n + , where n = 1 for An V and n = 2 for An VI . Effective charges in uranyl­(VI), for example, are +3.2e on U and −0.6e on O yl , i.e., [ 0.6– OU 3.2+ O 0.6– ] 2+ . , Condensed phase AAIs are prevalent for pentavalent actinyls like neptunyl­(V), , whereas less common for dipositive hexavalent actinyls due to greater Coulombic repulsion. , …”
Section: Introductionmentioning
confidence: 99%